Human capital and learning as a source of sustainable competitive advantage - Hatch, Nile W.; Dyer, Jeffrey H. (Strategic Management Journal, 2004)
Abstract This paper seeks to identify the sources of wide and persistent variations in learning performance in the semiconductor manufacturing industry. In the resource‐based view of the firm, human capital is frequently assumed to contribute to competitive advantage due to its inimitability based on its intangible, firm‐specific, and socially complex nature. Consistent with this view, we find that investments in firm‐specific human capital have a significant impact on learning and firm performance. More specifically, human capital selection (education requirements and screening), development through training, and deployment significantly improve learning by doing, which in turn improves performance. However, we find that acquiring human capital with prior industry experience from external sources significantly reduces learning performance. We also find that firms with high turnover significantly underperform their rivals, revealing the time‐compression diseconomies that protect firm‐specific human capital from imitation. These results provide new empirical evidence of the inimitability of human capital. Copyright © 2004 John Wiley & Sons, Ltd.